Pengembangan Bahan Ajar Matematika Berbasis Model Pembelajaran Jucama untuk Meningkatkan Kemampuan Pemecahan Masalah dan Kemampuan Komunikasi Matematis Siswa - Nur Fitriyana; Wahyu Widada; I Wayan Dharmayana (Jurnal Pendidikan Matematika:Judika Education, 2021)
The purpose of this study was to produce mathematics teaching materials based on the JUCAMA Learning Model to Improve Problem Solving and Mathematical Communication Skills of Students in Class VII SMPN 3 Sindang Kelingi, Rejang Lebong Regency. This research is a development research using a modification of the 4-D development model (Define, Design, Develop, Disseminate) which is limited to the 3rd stage. The subjects of this study were 30 students of Class VII SMPN 3 Sindang Kelingi, Rejang Lebong Regency. Based on the results of the study, it can be concluded that: Mathematics teaching materials based on the JUCAMA learning model are valid, practical, and effective. The results of the development of mathematics teaching materials based on the JUCAMA learning model can improve problem solving skills with an average achievement of 79.8% which is classically included in the high category and can improve mathematical communication skills with an average achievement of 81% which is classically included in high category. Conclusion. Mathematics teaching materials based on the JUCAMA learning model can improve students' problem solving and mathematical communication skills, besides that the teaching materials developed are valid, practical, and effective in orienting students through solving and proposing mathematical problems. Keywords: Learning Materials, Learning Model JUCAMA, Problem Solving Ability, Mathematical Ability Communication